Study on the characteristics of potassium salt international trade based on complex network - Wang, Mingyue; Kong, Rui (Journal of Business Economics and Management, 2019)
This paper studies the evolutionary characteristics of international trade of potassium salts. We construct a weighted and directed complex network model of potassium salt trade, analyze the scale and activity, trade relations, trade flow distribution and the importance of trading countries using UN Comtrade2000-2016 data. Results show that potassium salt trade is more dynamic, resource allocation is more convenient. Some countries have formed trade groups. The relationship between small and major countries is growing. The resource flows of countries with large degrees are conducive to balancing resource’s distribution. Besides Canada is a leading trade country, and the US, the Russian Federation, China and Brazil are trade-led countries. China, the Netherlands, the US, France and India are important hubs. Finally, using Porter's national competitive advantage theory, it proposes countermeasures for forming the international competitive advantage of potassium salt enterprises in different countries.